2019
DOI: 10.1016/j.mtla.2019.100233
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation and grain growth modelling in Ti-Nb microalloyed steels

Abstract: Mechanical properties of microalloyed steels are enhanced by fine precipitates, that ensure grain growth control during subsequent heat treatment. This study aims at predicting austenite grain growth kinetics coupling a precipitation model and a grain growth model. These models were applied to a titanium and niobium microalloyed steel. The precipitate size distributions were first characterized by TEM and SEM and prior austenite grain boundaries were revealed by thermal etching after various isothermal treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 39 publications
3
30
0
Order By: Relevance
“…(Ti,Nb)C precipitates are made responsible for pinning austenite grain boundaries. Due to the thermodynamic calculations presented in [31], it can be concluded that the (Ti,Nb)C precipitates are present at 1000 °C and 1100°C and dissolve at 1200 °C and higher temperatures. The microstructures are analyzed by means of software Fiji [48].…”
Section: Pinning Of Microstructural Entitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…(Ti,Nb)C precipitates are made responsible for pinning austenite grain boundaries. Due to the thermodynamic calculations presented in [31], it can be concluded that the (Ti,Nb)C precipitates are present at 1000 °C and 1100°C and dissolve at 1200 °C and higher temperatures. The microstructures are analyzed by means of software Fiji [48].…”
Section: Pinning Of Microstructural Entitiesmentioning
confidence: 99%
“…This must be seen under the precondition that the grain boundary arrangement is kept at the same conditions for the whole process. Recently, Graux et al [31] published optical micrographs of steel soaked at 1000 °C, 1100 °C and 1200 °C. While the austenite grains at 1000 °C and 1200 °C seem to be unimodally distributed, the grains at 1100 °C exhibit a deviation from the unimodal distribution.…”
Section: Pinning Of Microstructural Entitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…With (8) and (9) kept in mind, equation: D J Yet, it is difficult to make use of Eq. (10) since even in case of the single type of the barrier particles accurate determination of their dimensions and volume fraction [17] is rarely possible. That is why, to allow for Zener's pressure in empirical models, a virtually ultimate grain size D lim is introduced:…”
Section: Model Descriptionmentioning
confidence: 99%
“…The normal grain growth exerts a notable effect on the austenite microstructure during hot rolling and strongly influences the microstructures of the heat affected zone in weld joints of steels. Owing to the practical significance of this phenomenon, it has attracted attention in many original works [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] and in monographs [18,19]. Grain growth is conventionally expressed [1][2][3][4][5][6][7] by the equation:…”
Section: Introductionmentioning
confidence: 99%